The influence of vitamin B1 and zinc sulphate to the polysaccharide production of shiitake mushroom (Lentinus edodes) and the immunomodulatory test on lymphocyte cells of Balb/c mice - Sasmito, Ediati; Nugroho, Agung Endro; Wijaya, Chyntia Resti (Indonesian Journal of Pharmacy, 2005)
Mushroom had been used for a long time as medicine. Shiitake (Lentinus edodes) which is known as one kind mushroom of wood, has very large benefit and various advantages. Shiitake consist of polysaccharide, which is known as lentinan, arrange on shape Î²-1,3 glucan with Î²-1,3 and Î²-1,6 glucopyranoside having immunomodulatory properties. These properties are important for treatment of tumor and cancer. The purpose of this research is to increase polysaccharide production in shiitake by adding various concentration of vitamin B1 and 1 mMol zinc sulphate which are known as cofactor on enzymatic reaction of polysaccharide metabolism via pentose phosphate pathway. These cofactor are added on the media of primordial phase of shiitake cultures.The concentration of polysaccharide was determined by modified phenol sulphuric acid test (AOAC Official Method of Analysis No. 988.12) and the immunomodulatory test was conducted by employing lymphocyte cells and the proliferation of these cells was determined by MTT reduction method. The result showed that the maximum production of polysaccharide was reached by adding 8% of vitamin B1 and this was followed by the increase of lymphocyte cells proliferation activity.Key words: shiitake, vitamin B1, zinc sulphate, polysaccharide, lymphocyte, proliferation.